Effekter av spädningsvätska på motilitet och fertilitet hos hingstsperma - Ryytty, Kaisa (2009)
At SLU, Divison of Reproduction, Dept of Clinical Science, there is an ongoing project on the development and evaluation of new methods for the assessment of stallion semen quality. This EEF-study, which is a part of that larger project, has focused on the effects on motility and fertility of stallion semen of two different extenders and selection. Both an objective method and a subjective method for analysis have been used and compared in the study.